PENGEMBANGAN MEDIA PEMBELAJARAN MISITAYA (MINIATUR SISTEM TATA SURYA) UNTUK MENINGKATKAN PEMAHAMAN KONSEP IPAS KELAS VI SD NEGERI SURYODININGRATAN 2 - Angga Bayu Setiawan; Arip Febrianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to develop a learning media called Misitaya (Miniature Solar System) and produce a medium that is feasible, practical, and effective in enhancing students' conceptual understanding in IPAS (Science and Social Studies Integration). This study uses the Research and Development (RnD) method referring to the ADDIE development model. The research was conducted at SD Negeri Suryodiningratan 2. The limited trial subjects were 8 sixth-grade students, while the field trial subjects were 20 students in the control class and 20 students in the experimental class. Data collection instruments included observation, interviews, questionnaires, and tests. Data analysis techniques used were qualitative data analysis and descriptive quantitative analysis. There search findings show that: (1) Misitaya received a feasibility score of 90.6% from material experts and 93.3% from media experts, indicating a "very feasible" category. (2) Practicality based on teacher responses was 89.3% and student responses 92.5%, indicating "very practical." (3) The results of the t-test between pretest and posttest scores showed a significance value of 0.000 < 0.05, which means there is a significant difference between the pretest and posttest results. The experimental class average score was higher than that of the control class. Therefore, Misitaya is proven to be feasible, practical, and effective for use in classroom learning for students.